Research of rise of coherentness of treatment of signals at active radiolocation on the basis of algorithms of adaptive filtration - Babiy, Juliya; Karpova, Lesya; Kolesnik, Maksim (Видавництво Львівської політехніки, 2012)
The method of forming of radiolocation portraits of aims (RLPA) is examined on the basis of algorithms of adaptive signals processing, utilizing of what gives an opportunity to implement radar identification of aims and realize coherent processing of signals at application of non- coherence sources of sounding signals.
Keywords: Impulsive radio signal; radiolocation portraits of aims; inlying modulation; instability; optimum reception; filter; correlating